2016
DOI: 10.1002/cmr.b.21323
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Magnetic Field Gradient Waveform Monitor Technique and Consequent Accuracy of Pre‐Equalized Gradient Waveform

Abstract: The magnetic field gradient waveform monitor (MFGM) technique permits characterization of the temporal evolution of magnetic field gradients in magnetic resonance (MR) instruments (MRIs). Knowledge of the gradient waveform performance permits the development of further techniques, such as gradient waveform pre‐equalization, that correct and optimize gradient waveform distortions due to eddy currents induced during the application of switched magnetic fields and other system limitations. The accuracy of the MFG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Such a predistortion technique can be described as “pre‐equalization” or “pre‐emphasis,” and is also used in many signal processing applications apart from MRI to precompensate distortions in signals. In MRI, the possibility of a predistortion technique, which aims to calculate the input gradient waveform needed to produce the ideal waveform, was presented in Ref , and the accuracy was investigated . However, the technique has not yet been applied to MRI sequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a predistortion technique can be described as “pre‐equalization” or “pre‐emphasis,” and is also used in many signal processing applications apart from MRI to precompensate distortions in signals. In MRI, the possibility of a predistortion technique, which aims to calculate the input gradient waveform needed to produce the ideal waveform, was presented in Ref , and the accuracy was investigated . However, the technique has not yet been applied to MRI sequences.…”
Section: Introductionmentioning
confidence: 99%
“…In MRI, the possibility of a predistortion technique, which aims to calculate the input gradient waveform needed to produce the ideal waveform, was presented in Ref 20, and the accuracy was investigated. 21 However, the technique has not yet been applied to MRI sequences.…”
mentioning
confidence: 99%
“…The proposed SPI‐based gradient measurement technique does not require any special hardware, unlike other reported methods for PGM and MFM that need specialized equipment such as NMR field probes . Although these methods have been shown to be viable techniques to measure gradient waveforms, the use of external hardware adds complication and may be cost‐prohibitive.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the phase accumulated during the RF pulse can be interpreted by adding a time evolution phase term associated with the RF pulse application to the nominal phase accumulated during the phase encoding time t p . Simulations by Goora et al indicated that this additional phase term has the same sign as that of the phase — γGxtpx. This additional phase can be defined with an effective pulse duration teff as shown in Equations and .…”
Section: Theorymentioning
confidence: 98%
“…These factors suggest that additional phase accumulation alters the spatial information in phase encoding experiments and could lead to distortion of the reconstructed images. Recent work by Goora et al with related measurements of magnetic field gradient waveforms has motivated a reconsideration of this effect. Prior experiments conducted neglecting the phase accumulation during the RF pulse have been uniformly successful, suggesting that any effect on images obtained is minimal.…”
Section: Introductionmentioning
confidence: 99%